Relevansi Demokrasi Hukum dalam Konteks Siyasah Syar’iyyah Sekarang dan Akan Datang di Indonesia - Syaflin, Syaflin (Hakamain: Journal of Sharia and Law Studies, 2022)
Democracy is one interrested topic of discussions especially in relation to Islam. Many questions emerge associated with Islam and democracy such as: Does Islam has the concept of democracy? Does democracy compatible with Islam? What is the Muslim scholars response to the issue of democracy? This paper will investigates these questions using library research. This study discoveres that there are different opinions among Muslim scholars in relation to democracy: some said that democracy is compatible with the Islamic doctrine, another scholars stated otherwise, while the others stand between the two. Islamhas a term that resemble with the term democracy that is shurā, with different principles. In regard to the application of democracy in Indonesia, the majority of Muslim scholars in Indonesia accept positively to the concept of democracy and considered it to be compatible with the Islamic doctrine.